Borneol-triarylcorrole hybrids with chiral-optical response and anticancer behaviours. (November 2021) - Fu, Bo; Wang, Lin; Yu, Xiaoxiao; Fang, Xianying; Mack, John; Dingiswayo, Somila; Nyokong, Tebello; Liang, Xu; Xu, Haijun
Abstract: A series of four multifunctional A2 B type H3 corroles with meso -borneol substituents at the B position have been synthesized and characterized. A detailed analysis of the optical properties was carried out, and a comparison was made with theoretical calculations to identify the key trends in the structure-property relationships. The meso -borneol substituent couples with the corrole core leading to clear CD signals in the B band region. Enhanced anti-cancer properties are observed in vitro relative to (−)-borneol with cell inhibition rates of up to 94%. Highlights: Four corrole derivatives with meso-borneol substituents at the B position were developed. The photophysical characterizations were performed. The excitation coupling between the borneol-substituents and the corrole core was investigated by CD. 3d shows a good antitumor activity against HepG2 cells up to 94% .